ANALISA MANFAAT SISTEM SIKOPDIT PADA CREDIT UNION SATU HATI MENGGUNAKAN METODE INFORMATION ECONOMICS - Ignatius Novianto Hariwibowo; Albertus Pranowo (Universitas Sanata Dharma, 2021)
Many benefits obtained from information technology encourage financial institutions to invest in information technology, namely SIKOPDIT, one of which is Satu Hati Credit Union. In information technology investments, CU. Satu Hati has not yet done a proper calculation of benefits due to the difficulty of calculating the value of benefits from the application of information technology. This problem causes the investment to become a burden borne by the company. This community service aims to find out the benefits of the technology that has been implemented by CU. One heart. An assessment of the benefits of information technology requires methods that can analyze the financial and non-financial benefits of these investments. Therefore researchers used the information economics method to examine the level of eligibility. The result of this dedication was the application of SIKOPDIT to CU. Satu Hati is in quadrant A, which is an investment. In the Return on Investment (ROI) calculation, the value is 528%. The results of the calculation of the information economics scorecard obtained 69.8 results mean that this investment into the feasible category or the application of SIKOPDIT has provided benefits.